Analisis Akuntabilitas Kerja Aparat Pemerintah pada Kantor Desa Palippu Kecamatan Tanasitolo Kabupaten Wajo - Andi Supriadi; Sofyan Marzuki; Burhanuddin Burhanuddin (Politeknik Kampar, 2025)
This study aims to analyze the accountability of government officials at the Palippu Village Office, Tanasitolo District, Wajo Regency. Accountability is a crucial pillar in realizing transparent, effective, and responsible village governance. Village government officials are required not only to be able to carry out administrative duties but also to demonstrate openness, moral responsibility, and a willingness to be evaluated by the community. Therefore, this study focuses on the extent to which village officials' accountability has been implemented in accordance with the principles of good governance. The research method used is descriptive qualitative, with data collection techniques through in-depth interviews, direct observation, and documentation of various village government activities. The analysis focuses on five indicators of accountability: responsibility, transparency, answerability, implementation of sanctions and rewards, and evaluation mechanisms. The results of the study indicate that efforts towards accountability have begun to be visible, particularly in the aspects of transparency and development of village officials. Information regarding activities and the use of village funds is conveyed to the community through certain forums, although not yet fully distributed. Officials also show a willingness to be accountable, but in practice, the implementation of sanctions for violations has not been optimal. In contrast, the awards given are still informal and not yet part of a structured system. Performance evaluation of village officials is also limited and lacks active community participation. Therefore, this study recommends increasing the human resource capacity of village officials through training, strengthening the periodic evaluation system, and involving the community in monitoring public services. Implementation of these policies is expected to increase the accountability of village officials, thereby strengthening public trust in village government and improving the quality of public services.